2003
DOI: 10.1046/j.1365-2923.37.s1.10.x
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and integration of simulation-based learning technologies into the curriculum of a UK Undergraduate Education Programme

Abstract: Learning resources, in the form of simulators and computer-based learning modules, developed in one country can be successfully adopted and implemented in another. Facets that facilitated the adoption included close liaison between the developers of the resources in the USA and the implementers in the UK, and careful and systematic planning including in-depth integration of the simulation-based resources into the required curriculum rather than their relegation to a peripheral ad hoc position. The successful u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 17 publications
(16 reference statements)
1
32
0
1
Order By: Relevance
“…3,6,[11][12][13][14][15] Anesthesia has been and remains among the leading specialties in the field, and the number of anesthesia simulation centres worldwide is increasing exponentially. 1 The University of Toronto has over a decade of experience with simulation based education.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,[11][12][13][14][15] Anesthesia has been and remains among the leading specialties in the field, and the number of anesthesia simulation centres worldwide is increasing exponentially. 1 The University of Toronto has over a decade of experience with simulation based education.…”
Section: Discussionmentioning
confidence: 99%
“…Although logical, there is little evidence in the literature to support the broad applicability of these recommendations. Other authors have reported on their successful CAI integration experiences (Issenberg, Pringle, Harden, Khogali, & Gordon, 2003;Leong, Baldwin, & Adelman, 2003;Reeves, Aschenbrenner, Wordinger, Roque, & Sheedlo, 2004), but many questions remain for educators considering adding CAI to their course. We are aware of no publications that compare integration strategies or that study integration in differing settings, nor are there reports on the level of effort course directors should expect to commit to integrate a CAI program and to maintain it as a part of their course.…”
Section: Computer-assisted Instruction In Clinical Educationmentioning
confidence: 99%
“…54 Simulation tools include computer-based systems, 55,56 manikins 57 and biometric body parts for practice of invasive procedures, 58 and actors playing the role of patients to provide both training and assessment. 59 Patient simulation is used to some extent in virtually all Australian curricula.…”
Section: Flinders Universitymentioning
confidence: 99%